Working Arrangements for the Welfare and Protection of Adult Victims and Potential Victims of Human Trafficking and Modern Slavery : Guidance issued by the Department of Justice, the Police Service of Northern Ireland and the Health and Social Care Board.: Guidance issued by the Department of Justice, the Police Service of Northern Ireland and the Health and Social Care Board. (2018) - Northern Ireland., Department of Justice,; Northern Ireland., Health and Social Care Board,; Police Service of Northern Ireland,
No abstract available